Strategi PQ4R Strategi PQ4R Terintegrasi Model Team Quiz Berbasis E-Learning dalam Memberdayakan Keterampilan Berpikir Kritis dan Aktivitas Siswa - Asy'ari Asy'ari; Muhammad Saefi; Fahmi Cholid (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to provide light on various aspects of education, including student activities and critical thinking, as well as the implementation of PQ4R learning methodologies. True Experiment study is conducted using a quantitative research methodology. A control group with a pretest-posttest design was used in the study. Probability sampling is a technique used in sampling that allows for population analysis. Class X SMA Muhammadiyah 10 Surabaya was the random sequence used to choose the sample using the lottery method. Written tests and observations served as the data collection methods. Descriptive and statistical T-tests were used in data analysis. The study's findings indicate that there are two categories for how well learning is implemented: fairly good and extremely good. This study demonstrated that learning strategies had an impact on students' critical thinking skills by using statistical tests with a significant level of 0.05 and a significant value of 0.00 to show that Ha was accepted and Ho was rejected. According to data on student learning activities, the first meeting scored an average of 81.8, which is in the "very good" category. Therefore 66.9 is generally considered to be "good." The second meeting qualified as "very good" with an average score of 92.5. According to the research, the implementation of learning management utilizing the PQ4R technique along with the Quiz Team model on critical thinking abilities and student activities at Meeting 1 and Meeting 2 fell into the Pretty Good and Very Good categories, respectively. Keywords: Student Activity, Critical Thinking Ability, PQ4R Strategy, Team Quiz